Peran Solo International Performing Art (SIPA) Sebagai Penguatan Branding Solo The Spirit Of Java - Nur Dewati; Dr. Meitolo Hulu, S.ST., M.M. (Journal of Event, Travel and Tour Management, 2023)
Solo International Performing Art (SIPA) is a tourism event held in Solo, Central Java. SIPA is one of the pioneers and a legendary event and continue for 15 years. SIPA is a leading event, involving international delegations and becoming the icon of the Solo City cultural festival. The Solo Government has the brand “Solo The Spirit Of Java” which has been used for 17 years and is still considered very relevant. This research wants to see how SIPA as a leading event contributes to strengthening the branding "Solo The Spirit Of Java". This study uses a qualitative descriptive approach, data obtained by in-depth interviews with purposive sampling of key informants, SIPA CEO, SIPA Manager, Tourism Office and Festival Activists. The results showed that SIPA strengthened Solo city branding through various things, namely Javanese cultural content at the SIPA event, event themes, event locations, promotional materials and event publications which were carried out massively and highlighted Solo as a Javanese cultural city. The use of the ornament branding "Solo The Spirit Of Java" in the design and implementation of the event becomes an inseparable identity. SIPA strengthens Solo's branding as a leading event that is promoted internationally throughout the year by collaborating across stakeholders and involving volunteers (SIPA community), media and community partners. SIPA has succeeded in encouraging tourist visits to Solo through holding events for both domestic and foreign tourists. Expert opinion says that SIPA strengthens solo branding through display and content.